Analysis of the serve and the serve return in Squash at the men`s elite level - Carboch, J.; Strnad, J. (Journal of Physical Education and Sport, 2017)
Serving and receiving players have various possibilities of how and where to play their shot. The aim is to find out frequency and the most effective types of the serve and returns in professional squash. We have observed and analysed 15 matches involved in the tournament of the PSA World Series (Professional Squash Association) - Canary Wharf Squash Classic 2014. Notational analysis was based on shots type in the first two shots of the rally; i.e. a serve type, a return type including its placement, and the effectiveness (the relation of the serve and the return to the result of the rally). In 83% players used a forehand sidewall serve or a backhand sidewall serve with similar effectiveness, while they more often served from the right side of the court. Players received the serve on the volley in 72% (42% effectiveness), compared with receiving the serve after the bounce (37% effectiveness). The received ball was returned to the back court in 80%, 54% out of that was a straight drive, 46% was a cross-court drive, and the ball was more often directed to the opponent`s backhand side (61%). From the player`s angle of view, a more effective return shot was directed to the back left-hand corner (i.e. to the opponent`s backhand side). When receiving on the right side, a shot played to the back left-hand corner (from the player`s view) is more effective by 10% than a straight drive, which is, however, used more frequently despite its lower effectiveness. Coaches and players should know this kind of information and use more frequently a cross-court drive to the back court as a return shot than a straight drive to the back court in training and matches